The anti-corrosion performance of water-borne paints in long term tests - Roselli, Sol Natacha (2017)
One of the most inexpensive and effective method to protect steel against corrosion is paints containing active pigments. The traditional way to test these coatings performance is by accelerated tests (exposition to salt spray and/or humidity chambers) and electrochemical tests (corrosion potential, ionic resistance and electrochemical impedance spectroscopy). However, these tests give incomplete information if the results are not correlated to outdoor or service tests. The aim of this work was to evaluate water-borne epoxy anticorrosion paints containing different commercial phosphate pigments. The paints were exposed to a semi-industrial atmosphere for 7 years. Electrochemical tests and accelerated assays were also done in order to find a correlation between laboratory and service tests. The results obtained showed no correlation between those from pigment suspensions and those from painted panels, as it seemed that paint performance is highly dependent on the resin. The pigments zinc iron phosphate and zinc aluminium phosphate performed poorly in pigment suspensions. However, the coatings containing them exhibited the highest ionic resistance, the lowest film capacitance and gave the better results in outdoor tests. Results in outdoor exposure tests correlated with those from impedance measurements.